The Effect of Collaborative Strategic Reading (CSR) on 11th Graders Analytical Text Reading Comprehension - Shevanka Rahma Ayunda; Retno Wulan Dari (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Reading comprehension is considered a crucial skill in the learning of English as a Foreign Language (EFL); however, students at State Senior High Schools (MAN) still frequently struggle to understand analytical texts that require higher-order thinking skills. This study was conducted to examine the extent of the effect of Collaborative Strategic Reading (CSR) on the analytical text reading comprehension skills of 11th-grade students at MAN 1 Lamongan, as well as to identify improvements in aspects of reading comprehension after CSR was implemented. A quantitative approach with a quasi-experimental design was used in this study. A total of 51 11th-grade students were involved, with 28 students placed in the experimental group and 23 students in the control group. A validated and reliable analytical text reading comprehension test was used to collect data through pre-tests and post-tests. Data analysis was conducted using SPSS version 27 through descriptive statistics, an independent samples t-test, and repeated measures ANOVA. The results showed that the experimental group achieved a higher mean post-test score (84.97) compared to the control group (78.07), and a significant difference between the two groups was found via the independent samples t-test (p < 0.05), with a moderate effect size (Cohen’s d = 0.72). Significant improvements in various aspects of reading were also found in the experimental group, particularly in the ability to identify main ideas and draw conclusions. Overall, it can be concluded that CSR can provide structured and collaborative reading activities, thereby supporting improvements in EFL students’ comprehension of analytical texts as well as the development of specific comprehension subskills in the classroom.